Desenvolvimento de procedimentos alternativos de preparo e de determinação de metais pesados em fármacos tricíclicos - Barin, Juliano Smanioto (2007)
In this work, sample preparation and determination methods described in pharmacopeias were evaluated and alternative methods using sample decomposition in closed vessels and determination by atomic spectrometrometry were proposed as alternative. Tricyclic drugs (carbamazepine, amitryptyline hydrochloride and imipramine hydrochloride) were used to evaluate the methods. Pharmacopeial methods showed poor results for both sample preparation and determination methods. Many elements were lost during the decomposition in a muffle furnace and an incomplete decomposition was observed by wet digestion. For determination, the precipitation of analytical solutions of Ag, As, Bi, Cd, Cu, Hg, Mo, Pb, Sb and Sn with sulfide ion were suitable only for Ag and Pb. Therefore, some methods of sample preparation and heavy metals determination were evaluated. The microwave-induced combustion (MIC) with 7 mol L-1 HNO3 as absorbing solution was suitable for all elements with recoveries between 80 and 110%. The wet digestion of carbamazepine samples with HNO3 using the high pressure asher system (HPA) was efficient only at 320 °C by 3 h. If lower temperatures in HPA or microwave-assisted disgestion systems were used a incomplete digestion was obtained with a residue formation. These residues were caracterized by UV, HPLC, IV and RMN (1H and 13C) and a nitrated tricyclic structure could be pointed out. For amitryptyline hydrochloride and imipramine hydrochloride samples the dilution in water or diluted HNO3 was suitable for determination of heavy metals by GF AAS, ICP-OES and ICP-MS. However, for carbamazepine samples only two possibilities were found: the decomposition by MIC and determination by ICP-MS or the determination by directly solid sampling GF AAS.